Asymptotic Stability of Differential Equations with Infinite Delay - D. Piriadarshani; T. Sengadir (Journal of Applied Mathematics)
A theorem on asymptotic stability is obtained for a differential equation with an infinite delay in a function space which is suitable for the numerical computation of the solution to the infinite delay equation.